(untitled) (Al-Aasar, 2025)
Judicial activism as a topic has been controversial as both a legal and political issue especially in regards to its validity and effectiveness as a means of protecting human rights in Pakistan and similar developing nations. The role of judicial activism as an effective instrument for safeguarding human rights in Pakistan is further evaluated in this study. The study includes the jurisprudential principles of judicial activism, such as its integration with the law, judicial activism, and the division of authority. In what ways do Pakistani courts utilize the American doctrine of judicial activism to achieve justice? This is the question that guides the analysis of case law, constitutions, and court rulings in Pakistan. The study reveals that judicial activism is a critical device in addressing executive and legislative deficiencies in governance, assuming it is exercised within reasonable constitutional limits. This study also analyzes the issues confronting the judiciary in most developing countries like Pakistan such as excessive governmental control and inadequate autonomy. This paper attempts to address the debate around judicial activism by advocating for such activism while observing the limits of constitutions and ensuring compliance with stated human rights provisions.